2021
DOI: 10.1038/s41396-021-00980-4
|View full text |Cite
|
Sign up to set email alerts
|

Chlorine disinfection facilitates natural transformation through ROS-mediated oxidative stress

Abstract: The bacterial infection that involves antimicrobial resistance is a rising global threat to public health. Chlorine-based water disinfection processes can inactivate antibiotic resistant bacteria. However, at the same time, these processes may cause the release of antibiotic resistance genes into the water as free DNA, and consequently increase the risk to disseminate antibiotic resistance via natural transformation. Presently, little is known about the contribution of residual chlorine affecting the transform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(61 citation statements)
references
References 59 publications
2
59
0
Order By: Relevance
“…Previous studies have reported that antibiotics can damage cell envelope or block cell membrane synthesis to increase cell envelope permeability and then promote gene transfer by transformation [49,50]. Recent studies also ascribed the increased transformation frequency to the increased cell envelope permeability by disinfectant chlorine [41,51].…”
Section: Mechanisms For Enhanced Transformation By Artificial Sweetenersmentioning
confidence: 99%
“…Previous studies have reported that antibiotics can damage cell envelope or block cell membrane synthesis to increase cell envelope permeability and then promote gene transfer by transformation [49,50]. Recent studies also ascribed the increased transformation frequency to the increased cell envelope permeability by disinfectant chlorine [41,51].…”
Section: Mechanisms For Enhanced Transformation By Artificial Sweetenersmentioning
confidence: 99%
“…Additionally, multidrug (multidrug_transporter, mex E, sme B, sme C, sme D, sme E, and sme F), aminoglycoside [ aad A, aph (6)-1, aph (3’)-IIb], beta-lactam (metallo-beta-lactamase, TEM -1, TEM -117, TEM -157, TEM -187, TEM -205, TEM -75, TEM -91, and TEM -118), and rifamycin (rifampin monooxygenase) were enriched. With respect to the phenomenon that some ARGs increased after chlorine disinfection, some researchers have pointed out that free chlorine could promote the transformation of ARGs through a series of cell responses, for example, raising levels of reactive oxygen species (ROS), ROS-mediated DNA damage, and bacterial membrane damage ( Zhang et al, 2021 ). Our results indicated that chlorination reduced the diversity of the ARG types.…”
Section: Resultsmentioning
confidence: 99%
“…In Table 2 , DEGs encoding outer ( sthB , invG , yohG , apeE , yaiU ) and inner membranes ( ydgK , yddG , yeiH , yhjD ) were upregulated. This may be due to the cellular response induced by NaClO stress on Salmonella leading to cell membrane disruption and thus stimulating the expression of genes associated with cell membrane proteins ( Zhang et al., 2021 ). Xiao et al.…”
Section: Discussionmentioning
confidence: 99%